Elucidation of the possible mechanism of analgesic actions of butanol leaf fraction of Olax subscorpioidea Oliv. (6th March 2017) - Odoma, Saidi; Umar Zezi, Abdulkadir; Mohammed Danjuma, Nuhu; Ahmed, Abubakar; Garba Magaji, Muhammed
Abstract: Ethnopharmacological relevance: Preparations of Olax subscorpioidea have been used traditionally for the management of pains, inflammatory diseases, yellow fever, cancer and rheumatism. Previously, the analgesic activity of its leaf extract have been reported. Furthermore, an analgesic assay guided fractionation showed that the butanol soluble fraction is the most active. However, the mechanism of this activity remains to be elucidated. This present study investigated the possible pharmacological mechanisms involved in the analgesic activity of the butanol leaf fraction of Olax subscorpioidea (BFOS) using the acetic acid induced writhing test in mice. Materials and methods: Animals were orally administered distilled water (10 ml/kg), BFOS (1, 000 mg/kg) and morphine (10 mg/kg) 60 minutes before i.p administration of acetic acid and the resulting writhing were counted for 10 minutes. To establish the possible mechanism(s) of action of BFOS, separate group of animals were pretreated with naloxone (2 mg/kg, i.p ), prazosin (1 mg/kg, i.p ), yohimbine (1 mg/kg, i.p ), propranolol (20 mg/kg, i.p ), metergoline (2 mg/kg, i.p ), glibenclamide (5 mg/kg, i.p ) andl -arginine (50 mg/kg, i.p ) 15 minutes before BFOS. Results: BFOS and morphine showed marked analgesic activities ( p <0.001); the pretreatment of animals with naloxone, metergoline and l-arginine significantly ( p <0.05 and p <0.001) reduced the analgesic activity of BFOS; however, pretreatment with prazosin, yohimbine, propranolol and glinbenclamide showed no effect on its analgesic activity. Conclusion: Results obtained in this study suggest the involvement of opioidergic, serotonergic and nitric oxide-l-arginine pathways in the analgesic effect of butanol leaf fraction of Olax subscorpioidea . Graphical abstract: